Augmented Reality in Orthopedics: Current State and Future Directions - Chytas, Dimitrios; Malahias, Michael-Alexander; Nikolaou, Vasileios S. (Frontiers in Surgery, 2019)
Augmented reality (AR) comprises special hardware and software, which is used in order to offer computer-processed imaging data to the surgeon in real time, so that real-life objects are combined with computer-generated images. AR technology has recently gained increasing interest in the surgical practice. Preclinical research has provided substantial evidence that AR might be a useful tool for intra-operative guidance and decision-making. AR has been applied to a wide spectrum of orthopedic procedures, such as tumor resection, cartilage resurfacing, fracture fixation, enhancement of arthroscopic images, and component’s alignment in total joint arthroplasty. The present study aimed to summarize the current state of the application of AR in orthopedics, in preclinical and clinical level, providing future directions and perspectives concerning potential further benefits from this technology.